The WNT-controlled transcriptional regulator LBH is required for mammary stem cell expansion and maintenance of the basal lineage - Lindley, Linsey E. (Development, 2015)
The identification of multipotent mammary stem cells (MaSCs) has provided an explanation for the unique regenerative capacity of the mammary gland throughout adult life. However, it remains unclear what genes maintain MaSCs and control their specification into the two epithelial lineages: luminal and basal. LBH is a novel transcription co-factor in the WNT pathway with hitherto unknown physiological function. LBH is expressed during mammary gland development and aberrantly overexpressed in aggressive ‘basal’ subtype breast cancers. Here, we have explored the in vivo role of LBH in mammopoiesis. We show that in postnatal mammary epithelia, LBH is predominantly expressed in the Lin(−)CD29(high)CD24(+) basal MaSC population. Upon conditional inactivation of LBH, mice exhibit pronounced delays in mammary tissue expansion during puberty and pregnancy, accompanied by increased luminal differentiation at the expense of basal lineage specification. These defects could be traced to a severe reduction in the frequency and self-renewal/differentiation potential of basal MaSCs. Mechanistically, LBH induces expression of key epithelial stem cell transcription factor ΔNp63 to promote a basal MaSC state and repress luminal differentiation genes, mainly that encoding estrogen receptor α (Esr1/ERα). Collectively, these studies identify LBH as an essential regulator of basal MaSC expansion/maintenance, raising important implications for its potential role in breast cancer pathogenesis.